Real-time interactive visualization of information hierarchies - Adrian Rusu; Confesor Santiago; Radu Jianu (IV'07: Proceedings of the International Conference on Information Visualisation, 2007)
An information hierarchy is a collection of relational information that is arranged in a ranking organization where each entity is subject to a single other entity, except for the top (root) element. The usefulness of a visualization of an information hierarchy depends on its capability of conveying the information quickly and clearly. The interaction with the information hierarchy allows a user to further analyze its underlying structures and relationships, which is essential for the effectiveness of the visualization. In this paper we present a novel method to interactively visualize information hierarchies in real-time. We use the World Wide Web as an application example of our techniques. The result is a novel Web browsing and visualization method with an innovative combination of features: (i) Web data is retrieved and displayed in real-time (i.e. Web data is not pre-recorded), (ii) browsing and visualization are synchronized together in the same interface, (iii) tree-based visualization engine, and (iv) space-efficient display of visualization. Our study shows that users are able to orient themselves better in cyberspace and locate Web pages of interest faster.